Impact of musical training in specialised centres on learning strategies, auditory discrimination and working memory in adolescents - Sepúlveda-Durán, Carmen María; Martín-Lobo, Pilar; Santiago-Ramajo, Sandra (British Journal of Music Education, 2024)
The aim of this study was to analyse whether specialised musical training influences auditory discrimination, working memory, learning strategies and academic performance. Sixty students (30 with at least four years of musical training and 30 without) of the same socioeconomic level were compared. Significant differences were found between students with and without musical training in terms of learning strategies, working memory and academic performance (p= <.05). This study shows the benefits of musical training offered at specialised centres, the development of students’ cognitive skills and the contributions of neuroscience to improving professional practice.
Keywords: adolescence; auditory discrimination; keywords; learning strategies; musical training; working memory; Scopus; JCR